Improving the Usability User Experience of Peduli Lindungi Application based on Heuristic Evaluation - Erlina Wahyu Fadhilah; Anisa Herdiani; Ati Suci Dian Martha (Journal of Information System Research (JOSH), 2022)
Peduli Lindungi is an application developed to help relevant government agencies in tracking to stop the spread of COVID-19. Peduli Lindungi is expected to help the government in the tracking process to facilitate the detection of the reach of COVID19. However, over time, many complaints about the user experience written by users in the App Store and Play Store applications. This study uses the Heuristic Evaluation method to analyze usability. This method is used to get an evaluation of the shortcomings of usability. In this study, it was found that the usability of the Peduli Lindungi Application was good enough. However, there are still aspects that require improvement. This aspect is the Flexibility and Efficiency of Use with a severity rating of 3.8 and Aesthetic and Minimalist Design with a severity rating of 3.4. So that design improvements are made based on these aspects. The test was carried out and found that the Flexibility and Efficiency of Use had a severity rating of 1.5. While Aesthetic and Minimalist Design with a severity rating of 2.6. It is concluded that the design is better than before.